Inibidor de tripsina do tipo kunitz de sementes de Albizia lebbeck (L.) Benth. atrasa e prejudica o desenvolvimento de Aedes aegypti - Silva, Emanuel Francelino (2018)
Arboviruses such as dengue fever, zika fever and chikungunya fever and their severe complications have caused concern in health authorities due to the absence of an effective vaccine or a specific treatment. The chemical control of the vector of these diseases, Aedes aegypti (Diptera), presents disadvantages due to the adverse effects on human health, environment and also due to the resistance developed by the insects. In this sense, proteinase inhibitors can be an alternative to chemical insecticides because they inhibit the catalytic activity of proteolytic enzymes, such as trypsin, present in the midgut of Ae. aegypti. We purified and characterized a trypsin inhibitor from A. lebbeck seeds (AlTI) and investigated its effect upon Ae. aegypti egg hatching, larval development and digestive proteases. The molecular mass of the inhibitor was determined (21 kDa), characterizing it as kunitz type. The inhibitor was stable over a range of temperature (30–70 ºC). AlTI specifically inhibited bovine trypsin (99.3%) but showed not inhibitory activity against chymotrypsin and papain. AlTI (0.1 mg/mL) promoted 46.8% activity reduction of Ae. aegypti larvae midgut proteases. The AlTI (1.0 mg.mL-1) have no effect on egg hatching but delayed the development of the larvae in 5 days (62.2%) compared to the control (distilled water), in addition caused 53.3% of larvae mortality. Our results suggest the A. lebbeck trypsin inhibitor can be an alternative strategy to control the Ae. aegypti.